Improvement of Self Confidence of Orphanage Children in Entrepreneurship through Group Guidance Services at Aisyiyah Orphanage Nanggalo Padang Branch - Zutrina Tiara; Firman Firman (Jurnal Neo Konseling, 2019)
Based on the phenomenon of foster children who have been fostered at the orphanage is not yet economically independent and still dependent on others. They are confused about what to do after graduating from the institution which causes them to lack the courage to develop their own business with skills that have been taught at the orphanage. Increased self confidence of orphans in entrepreneurship is needed as a provision to meet life in the future. Increased confidence in the orphanage can be improved in a variety of ways, one of which is through the services in guidance and counseling, namely group guidance services. The purpose of this study was to examine the differences in self-confidence of orphanage children in entrepreneurship in the experimental group pretest andposttestfollowing group guidance services with the control group pretestandposttestwithout following group guidance services.This research was conducted at the Aisyiyah Orphanage in Nanggalo Padang Branch, with 20 research subjects. This research is a quantitative research with a quasi-experimental type of research with the non-equivalent control group design. To test the differences in self-confidence of orphanage children in pretest and posttest entrepreneurship were treated, data analysis was performed using the t-test assistance program SPSS version 20.00.The research findings show that there is a significant difference in the self confidence of orphanage children in the pretest and posttest experimental group entrepreneurs following group guidance services. There was no significant difference in self confidence of orphanage children in the pretest and posttest control group entrepreneurship without attending group guidance services. There was a significant difference in the self confidence of orphanage children in the pretest and posttest experimental group entrepreneurship following the group guidance service with the control group without following the group guidance service.